Bolаlаr Vа Kаttаlаrdа Nаfаs Olish Fiziologiyasi - Akbarova Muruvvat Sobirovna (Genius Journals, 2022)
In this article, we aimed to study and analyze the cases related to respiratory physiology in children and adults and to develop methods and methods that apply the right conclusions in our lives.
Keywords: Respiratory process; lung tissue; hiccups; bronchi